2022
DOI: 10.3389/fped.2022.915085
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Endoscopic Retrograde Cholangiopancreatography for Pediatric Hepato-Pancreato-Biliary Diseases: A Systematic Review and Meta-Analysis

Abstract: BackgroundHepato-pancreato-biliary (HPB) disease has different causes and types between children and adults, which has been increasingly diagnosed in the pediatric group. Endoscopic retrograde cholangiopancreatography (ERCP) has been gradually considered as a therapeutic method in adults, while in pediatric patients, there are not many reports of its usage. This systematic review and meta-analysis aims to assess the use condition of therapeutic ERCP in the management of pediatric HPB diseases.MethodsThis syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Nevertheless, the meta-analysis conducted by Sun et al in 2022 revealed a failure rate of 26%, which was notably higher than the rates recorded in our study and other similar research. However, the meta-analysis encompassed studies published until February 2022, potentially including earlier research conducted in settings with less advanced infrastructure and by operators with lower levels of expertise (27).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the meta-analysis conducted by Sun et al in 2022 revealed a failure rate of 26%, which was notably higher than the rates recorded in our study and other similar research. However, the meta-analysis encompassed studies published until February 2022, potentially including earlier research conducted in settings with less advanced infrastructure and by operators with lower levels of expertise (27).…”
Section: Discussionmentioning
confidence: 99%